Physiological and molecular mechanisms of Acacia melanoxylon stem in response to boron deficiency - Chen, Zhaoli; Bai, Xiaogang; Zeng, Bingshan; Fan, Chunjie; Li, Xiangyang; Hu, Bing (Frontiers in Plant Science, 2023)
Boron is an essential micronutrient for plant growth as it participates in cell wall integrity. The growth and development of Acacia melanoxylon stem can be adversely affected by a lack of boron. To explore the mechanism of boron deficiency in A. melanoxylon stem, the changes in morphological attributes, physiological, endogenous hormone levels, and the cell structure and component contents were examined. In addition, the molecular mechanism of shortened internodes resulting from boron deficiency was elucidated through transcriptome analysis. The results showed that boron deficiency resulted in decreased height, shortened internodes, and reduced root length and surface area, corresponding with decreased boron content in the roots, stems, and leaves of A. melanoxylon. In shortened internodes of stems, oxidative damage, and disordered hormone homeostasis were induced, the cell wall was thickened, hemicellulose and water-soluble pectin contents decreased, while the cellulose content increased under boron deficiency. Furthermore, plenty of genes associated with cell wall metabolism and structural components, including GAUTs, CESAs, IRXs, EXPs, TBLs, and XTHs were downregulated under boron deficiency. Alterations of gene expression in hormone signaling pathways comprising IAA, GA, CTK, ET, ABA, and JA were observed under boron deficiency. TFs, homologous to HD1s, NAC10, NAC73, MYB46s, MYB58, and ERF92s were found to interact with genes related to cell wall metabolism, and the structural components were identified. We established a regulatory mechanism network of boron deficiency-induced shortened internodes in A. melanoxylon based on the above results. This research provides a theoretical basis for understanding the response mechanism of woody plants to boron deficiency.